Algorithmic racism: a literature review (Research, Society and Development, 2023)
Algorithmic racism is a topic that has raised several discussions in the society we live in, as organizations make use of the excuse of profitability to institutionalize the structural racism that we see in our society. From the debate on this topic, we were able to propose real alternatives to combat this practice and mitigate this type of attitude on the part of the technology industry. The objective of this study was to present a discussion based on bibliographical sources that structure a project in higher education based on the theme that generates algorithmic racism. The methodological adornment for structuring the data occurs from an integrative literature review, allowing a connection between the author and the collected data for the qualitative development of his discussion. The results provide a reflection on the importance of this topic for today's society, which lives in a moment of transition where old customs are no longer well regarded by society and some are even criminalized. In this way, discussions like these are extremely important.